2013
DOI: 10.1016/j.juro.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy in Children with Cystine Stone: Long-Term Outcomes from a Single Institution

Abstract: Percutaneous nephrolithotomy is a safe and effective treatment for children with cystine stones. Our high recurrence and regrowth rates emphasize that our treatment schedule is inadequate to prevent recurrent cystine calculi. Additional investigation is needed to determine the optimal medical therapy for preventing recurrence and regrowth of cystine stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…In selected cases, especially if early diagnosis is possible, minimally invasive procedures allow excellent outcomes, improving patient quality of life while reducing morbidity. In another study evaluating 65RU in 51 children with large cystine stones (mean burden of 3.3cm 2 ) treated with PCNL, the stone free rate was 63.1% (41/65RUs) ( 15 ). After additional endoscopic procedures the final stone-free rate was increased to 73.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In selected cases, especially if early diagnosis is possible, minimally invasive procedures allow excellent outcomes, improving patient quality of life while reducing morbidity. In another study evaluating 65RU in 51 children with large cystine stones (mean burden of 3.3cm 2 ) treated with PCNL, the stone free rate was 63.1% (41/65RUs) ( 15 ). After additional endoscopic procedures the final stone-free rate was increased to 73.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Although shock wave lithotripsy is a safe procedure, however Shokeirs and their colleagues showed percutaneous nephrolithotomy is better than shock wave lithotripsy for treatment of 1 to 2 cm renal stones in children, yielding higher stone-free and lower re-treatment rates [11]. More ever Onal et al revealed the safety and efficacy of PCNL in pediatric patients with cystine stones resistance to SWL [12].…”
Section: Discussionmentioning
confidence: 99%
“…One previous study reported a complication rate associated with PCNL in patients with cystine stones of 15.4% [14]. Another study reported an overall complication rate of 23.8% for URS [15].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported an overall success rate of PCNL in children with cystine stones of 63.1% [14]. Another previous study reported a success rate of 71% in patients with cystine stones who underwent URS [15].…”
Section: Discussionmentioning
confidence: 99%